Invasive species management will benefit from social impact assessment. Issue 2 (14th November 2016) - Crowley, Sarah L.; Hinchliffe, Steve; McDonald, Robbie A.
Summary: Invasive species management aims to prevent or mitigate the impacts of introduced species but management interventions can themselves generate social impacts that must be understood and addressed. Established approaches for addressing the social implications of invasive species management can be limited in effectiveness and democratic legitimacy. More deliberative, participatory approaches are emerging that allow integration of a broader range of socio‐political considerations. Nevertheless, there is a need to ensure that these are rigorous applications of social science. Social impact assessment offers a structured process of identifying, evaluating and addressing social costs and benefits. We highlight its potential value for enabling meaningful public participation in planning and as a key component of integrated assessments of management options. Policy implications . As invasive species management grows in scope and scale, social impact assessment provides a rigorous process for recognising and responding to social concerns. It could therefore produce more democratic, less conflict‐prone and more effective interventions.